2012
DOI: 10.1097/nmc.0b013e31825a8aa5
|View full text |Cite
|
Sign up to set email alerts
|

Relief of Pain During Blood Specimen Collection in Pediatric Patients

Abstract: Use of external cold and vibration via Buzzy decreased perceived pain and reduced children's anxiety during blood specimen collection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
83
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(89 citation statements)
references
References 20 publications
5
83
1
Order By: Relevance
“…A relatively new devise the "BUZZY" (MMJ Labs, Atlanta, GA, USA), combines a cooling ice-pack and a vibrating motor, and has been found in four studies to date to decrease pain and to enhance patients' compliance during venous blood collection, venipuncture and IV insertion (Baxter, Cohen, McElvery, Lawson, & von Baeyer, 2011;Canbulat, Ayhan, & Inal, 2015;Inal & Kelleci, 2012;Whelan, Kunselman, Thomas, Moore, & Tamburro, 2014). The use of the "BUZZY" in the emergency department with 81 children aged 4-to 18 years who were randomized to the device (n = 41) or standard care (n = 40), found that the pain scores assessed on the Faces Pain Scale-Revised during venipunture were lower in the intervention group for both the children and their parents (Baxter et al, 2011).…”
mentioning
confidence: 99%
“…A relatively new devise the "BUZZY" (MMJ Labs, Atlanta, GA, USA), combines a cooling ice-pack and a vibrating motor, and has been found in four studies to date to decrease pain and to enhance patients' compliance during venous blood collection, venipuncture and IV insertion (Baxter, Cohen, McElvery, Lawson, & von Baeyer, 2011;Canbulat, Ayhan, & Inal, 2015;Inal & Kelleci, 2012;Whelan, Kunselman, Thomas, Moore, & Tamburro, 2014). The use of the "BUZZY" in the emergency department with 81 children aged 4-to 18 years who were randomized to the device (n = 41) or standard care (n = 40), found that the pain scores assessed on the Faces Pain Scale-Revised during venipunture were lower in the intervention group for both the children and their parents (Baxter et al, 2011).…”
mentioning
confidence: 99%
“…Oatey and Stiller after evaluating inpatients showed that 28 % agree that generally, the venipuncture procedure is painful [38]. The new tool called Buzzy Ò reportedly relieves the sensation of pain during venipuncture [8][9][10]. However our results showed statistically significant increase of several analytes when the blood specimens were collected using Buzzy Ò in comparison with the standard procedure (Table 1).…”
Section: Discussionmentioning
confidence: 62%
“…For private laboratories the level of patient satisfaction with the diagnostic blood collection service is a very important quality indicator. A new device called Buzzy Ò has been recently presented that combines a cooling ice pack and a vibrating motor in order to relieve the venipuncture pain in adults and children, thus aimed at increasing patient satisfaction during blood collection [8][9][10]. The aim of this study was to evaluate the impact of Buzzy Ò use during diagnostic blood specimens collection by venipuncture for routine immunochemistry tests.…”
Section: Introductionmentioning
confidence: 99%
“…It operates on the theory of gate control and descending noxious inhibitory control, using vibration and cooling to decrease the perception of pain at the procedure site when placed 3-5 cm proximally 30-60 s prior to the procedure. Buzzy® has been shown in some studies to be superior to placebo and to vapocoolants and analgesic creams (Baxter, Cohen, McElvery, Lawson, & von Baeyer, 2011;Canbulat, Ayhan, & Inal, 2014;Inal & Kelleci, 2012). There are drawbacks to each device.…”
Section: Background Knowledgementioning
confidence: 94%